PRESENCIA DEL PEZ LEÓN, PTEROIS VOLITANS (ACTINOPTERYGII: SCORPAENIDAE), EN EL DEPARTAMENTO DE LA GUAJIRA, MAR CARIBE DE COLOMBIA (Boletín de Investigaciones Marinas y Costeras, 2016)
The red lionfih was captured in the northeast Colombian Caribbean, in “El Yoyo” fihing ground, located in La Guajira peninsula (Riohacha). The Guajira continental shelf, located between Santa Marta and Venezuela, should be a stepping area for lionfih pelagic larvae.